Investigating the relationship between integrated reporting quality and its effect on risk of the top 100 JSE listed companies in South Africa - Jhavary, Husnaa (University of the Witswatersrand, Johannesburg, 2023)
This thesis investigates the relationship between the quality of an organization’s integrated report, as defined by the EY Integrated Reporting Awards, and the risk of the organisation. To achieve this the relationship between an entity’s financial ratios and the quality of the integrated report it produces are calculated and explored. A quantitative research approach is used and risk is proxied using debt and equity ratios collected from the IRESS database, as well as integrated reports found on the websites of the top 100 JSE-listed companies over five years from 2017 to 2021. A regression is performed using the Statistical Package for the Social Sciences (SPSS) software. The results suggest a significant relationship between the costs of debt and integrated reporting quality, when compared to the cost of equity and the weighted average cost of capital. In addition, other variables hold a stronger relationship with integrated reporting quality, such as the ability of a firm to produce a standalone CSR report, as well as the firm’s equity market-to-book ratio and a firm’s size
A research report submitted by In fulfillment of the requirements for the degree of Master of Commerce University of the Witwatersrand
Keywords: Risk; EY Integrated Reporting Award; JSE; Integrated reporting; Integrated reporting quality; South Africa; SDG-8: Decent work and economic growth